Accuracy of rapid point-of-care antibody test in patients with suspected or confirmed COVID-19. Issue 1 (January 2022) - Vancheeswaran, Rama; Willcox, Merlin Luke; Stuart, Beth; Knight, Matthew; Kandil, Hala; Barlow, Andrew; Patel, Mayon Haresh; Stockham, Jade; O'Neill, Aisling; Clark, Tristan W; Wilkinson, Tom; Little, Paul; et al.
Highlights: The rapid test for antibodies to SARS-COV-2 was 90.1% sensitive and 100% specific. This is comparable to reference antibody tests for prior infection with COVID-19. It could support clinical decision-making for patients with >10 days of symptoms. It would be useful in settings where vaccination is not widespread. And where PCR tests are not widely available.